Leadership and Conflict Management Training for HR Empowerment in Non-Profit Organizations - Ginting, Sunardi; Rakhmawati, Eni; Setyawan, Antonius Ary; Anantadjaya, Samuel PD; Nawangwulan, Irma M (TRANSFORMASI : JURNAL PENGABDIAN PADA MASYARAKAT, 2024)
Leadership and conflict management training play a crucial role in strengthening human resource (HR) empowerment within non-profit organizations. This study aims to assess the effectiveness of leadership and conflict management training in enhancing individual capabilities for conflict management and advancing HR potential in non-profit organizations. The method used is Community Service (PKM), with a hands-on approach and periodic competency evaluations. Through this training program, participants are provided with in-depth understanding of conflict dynamics and adaptive leadership techniques that help foster a harmonious and productive work environment. The outcomes of this activity indicate a significant improvement in participants' abilities to manage conflicts, enhance team collaboration, and actively contribute to the organization's goals. This training program is expected to serve as an effective model for HR empowerment in other non-profit organizations.